PENGOPTIMALKAN PENDEKATAN KEADILAN RESTORATIF DALAM MENANGGULANGI KEJAHATAN YANG DIAKIBATKAN GAYA HIDUP HEDONISME - Agung Salman Alfarisi; Ahmad Muhammad Ridwan Saeful Hikmat (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
There is no denying that technological development has grown rapidly and become more sophisticated, impacting on people's lifestyles. Poverty has been known to result in a high proportion of low-income offenders. In fact, the backlog of cases continues to grow every day, causing tremendous suffering for justice seekers. The purpose of this research is to see the extent of the implementation of restorative justice in repairing criminals caused by the hedonism lifestyle. This research is a normative legal research. The results of the study found that the current restorative justice approach with education and discussion can reduce the level of recidivism. Criminal law procedural justice must pay attention to human dignity and values, with the aim of repairing, educating, preventing repetition of crimes, and integrating offenders back into society. Thus, restorative justice aims to build a criminal justice system that is sensitive to the problems of victims and offenders from the effects of hedonism. This approach is a critique of the criminal justice system that tends to be retributive and ignores the role of victims, perpetrators, and society so that the individualization of offenders with the nature of hedonism becomes a focus in restorative justice.